Prevalensi dan Faktor yang Memengaruhi Kejadian Anemia pada Remaja Putri di Kota Makassar, Sulawesi Selatan - Andi Sitti Rahma; Rini Fitriani; Risma Irnawati; Afifah Az-zahrah (IAKMI South Tangerang Branch, 2024)
The Prevalence and Associated Factors of Anemia in Adolescent Girls in Makassar, South Sulawesi Background: Anemia is still a problem in Indonesia, and adolescent girls are at high risk of experiencing anemia. Objective: The research aims to determine the factors that influence the incidence of anemia in adolescent girls in Makassar City. Method: This research is a cross-sectional study involving 276 young women who met the inclusion and exclusion criteria. It used a purposive sampling method at seven senior high schools in Makassar City. Result: The research results showed that the incidence of anemia in adolescent girls in Makassar City was 29.3%. Factors that influence the incidence of anemia are the intake of foods/drinks that inhibit iron absorption, such as tea (p-value = 0.04), chocolate (p-value <0.01), dairy products (p-value <0.01), and degree of blood loss during menstruation (p-value = 0.03). Factors that did not influence the incidence of anemia were nutritional status (p-value = 0.47), the incidence of Chronic energy deficiency (CED) (p-value = 0.96), level of nutritional knowledge (p-value = 0.36), compliance with consuming blood supplement tablets (p-value = 0.23), and diet (p-value >0.05). Conclusion: The factors influencing adolescent anemia in Makassar City in 2023 are the intake of food/drinks that inhibit iron absorption and the degree of blood loss during menstruation.